Flexural performance of reinforced concrete beam strengthened with CFRP fabric and steel plate [microfilm] - Tan, Felix Han Tze (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006